An unkindness of ravens eaudiobook Inspector wexford mysteries series, book 13. - Rendell, Ruth (Chief Inspector Wexford Mystery, 2018)
Named as a life peer in the House of Lords in 1997, Ruth Rendell is also a Mystery Writers of America Grand Master and the winner of three Edgars and four Golden Dagger Awards. Her Inspector Wexford mysteries thrill audiences around the globe with their complex plots and nuanced characters. As a favor to his wife, Inspector Wexford agrees to investigate the case of a missing husband. After gathering evidence, Wexford seems pretty certain that Joy Williams' husband simply ran off with a younger woman. But when Rodney Williams is found stabbed to death, Wexford does a little more digging. It seems that the murder is tied to a militant feminist group working in the area. They call themselves the Arria and they've taken the raven as their symbol.